PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN PEMERINTAH DALAM PENANGANAN BENCANA KEBAKARAN HUTAN DAN LAHAN DI SEKITAR TAMAN NASIONAL BUKIT TIGA PULUH - Wirianto, Robby; M.Mardhiansyah, M.Mardhiansyah; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Bukit Tiga Puluh National Parks (TNBT) is a nature conservation area which the management are influence by people activities in the surrounding area. Public perception can be identified with an individual responsesto something they have been seen, heard, and felt in their environment.Forest and land fires always happens every year. One of the government effort to reduce the forest and land fires is by releasing a policy to handling the catastrophe of forest and land fires. Survey method is a way of collecting dara where the researcher or the data collector give a question or statement to the respondent either in verbally or in writing. There are 38 respondent taken 30 respondents from the three villages, and 8 respondents to the relevant institutions 2 respondents from National Park, 2 respondents from the forestry service and 4 respondents from non government organizations. The result showed that most of the villagers didn’t know about the government policy on forest and land fires. This research shows that 50% of Rantau Langsat villagers, 100% of Sungai Akar villagers, and 70% of Talang Lakat villagers didn’t know yet about the policy of the forest and land fires. Keywords: National Park, Forest and Land Fires, Policy, Public Perception